THE INFLUENCE OF PARENTAL DEMANDINGNESS ON MALE ADOLESCENT ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS - Macharia, Jane; Shikuku, Dr. Mulambula M (American Journal of Education and Practice, 2016)
Purpose: The purpose of this study was to determine the influence of parental demandingness on male adolescent academic performance in public secondary schools in Kiambu district. Methodology: The study used ex-post facto research design. Stratified sampling was used to select the participants in the study. Schools were stratified into single sex and co-education schools. Systematic sampling using the class lists was used to identify the students who constituted the sample. The research instruments were the students' questionnaire, the deputy principal's and the teacher counsellor's interview guide. The sample constituted 240 male students, six deputy principles and six teacher counselors. A pilot study was done to pre-test the research instruments so as to estimate their reliability and validity. Data collected was analyzed using Statistical Package for Social Sciences (SPSS). The findings were presented using descriptive and inferential statistics. Descriptive statistics included, frequency distribution, means, bar graphs, and tabulated according to the research objectives. Inferential statistics used included Chi Square and pearson correlation to test the hypotheses at 90% and 95% level of confidence; correlation coefficient was used to measure the strength of linear relationship between the variables of the study. Results: The results indicated that rebellious behaviour was positively and significantly correlated to parental demandingness. Unique contribution to theory, practice and policy: The study came up with a model that is recommended to schools for adoption by guidance and counselling teachers to help create awareness and understanding to both the students and parents with the aim of improving or bettering their relationship, academic performance and prevent rebellion in public secondary schools.